Alternative mitigating solutions based on inorganic nanoparticles for the preservation of cultural heritage - Corbu, Viorica Maria; Dumbravă, Andreea Ştefania; Marinescu, Liliana; Motelica, Ludmila; Chircov, Cristina; Surdu, Adrian Vasile; Gheorghe-Barbu, Irina; Pecete, Ionuţ; Balotescu, Irina; Popa, Marcela; Marinas, Ioana Cristina; Ianovici, Nicoleta; et al. (Frontiers in Materials, 2023)
Biodeterioration is a big challenge for the preservation of cultural heritage objects and for the community's safety, fostering the search for novel methods effective in removing microbial biofilms and subsequent biodeterioration. In this context, nanoparticles (NPs) are considered an interesting alternative, based on their unique physicochemical and biological properties. The present study aimed to evaluate the antimicrobial efficiency of Ag, Au, Cu and ZnO NPs against a significant number of filamentous fungi and bacterial strains isolated from wooden and stone cultural heritage objects from different Romanian regions, as well as from museum collections, with the final goal to establish their potential to develop novel preservation strategies, which high efficiency and low ecotoxicity. Six types of nanoparticles (NPs) based on Ag, Au, Cu, and ZnO were synthesized and characterized for their physico-chemical properties, ecotoxicity as well as efficacy against 75 filamentous fungi and 17 bacterial strains isolated from wooden and stone cultural heritage objects (XV-XIX centuries). The results showed that all synthetized NPs are homogeneous, demonstrating a good stabilizing coating, and have spherical or triangular shapes, with sizes between 9 and 25 nm. The highest antifungal efficiency has been recorded for AgNPs, followed by CuNPs and ZnONPs, the most susceptible strains being Aspergillus montevidensis, Penicillium commune, P. corylophylum, Bacillus megaterium and B. cereus. The CuNPs and ZnONPs decreased the capacity of microbial strains to adhere to the inert substratum. The influence of the tested NPs against enzymes/organic acids production varied depending on the NP types and by species. The obtained results are promising for the development of efficient and economical alternative solutions for the heritage preservation showing high antimicrobial activity against the prevalent fungal and bacterial strains involved in the biodeterioration of Romanian heritage objects.